State Treasury and Budget System Online Monitoring (OM-SPAN) on Organizational Performance - Puspitasari, Eka Firta; Baridwan, Zaki; Atmini, Saari (Interdisciplinary Social Studies, 2023)
Backgrounds: Prior to the adoption of the OM-SPAN program and its implementation, treasury officials must go to State Treasury Service Office (KPPN) to review the liquidation process through a Payment Order (SPM) and Fund Deposit Order (SP2D). Aim: This study aims to analyze and obtain empirical evidence on the effect of information quality, system quality, service quality, and trust on user satisfaction of the OM-SPAN application at the Treasury Officer of the Directorate General of Housing of the Ministry of PUPR. Furthermore, the effect of user satisfaction on organizational performance will also be analyzed. Methods: The sample consisted of 95 Treasury officials of the Directorate General of Housing of the Ministry of PUPR spread across work units and centers in 38 provinces in Indonesia. Findings: The findings and results of this study empirically show that user satisfaction with the OM-SPAN application is influenced by several factors, namely the information quality and system quality of the OM-SPAN application. The results of this study also concluded that user satisfaction with the OM-SPAN application has a positive effect on organizational performance. The findings and results of this study also make it clear that no empirical evidence explains the effect of service quality and trust as determinants of OM-SPAN application user satisfaction.